2017
DOI: 10.1093/jnen/nlx001
|View full text |Cite
|
Sign up to set email alerts
|

Immune Cell Infiltrates in Hippocampal Sclerosis: Correlation With Neuronal Loss

Abstract: Immune mechanisms have been increasingly recognized in the pathogenesis of hippocampal sclerosis (HS), but infiltration of cytotoxic T-cells and its pathological significance in patients with HS has not been explored. We examined 30 cases of surgically resected hippocampi, including 16 International League Against Epilepsy (ILAE) type 1, 9 ILAE type 2, 1 ILAE type 3 HS, and 4 ILAE No-HS, as well as 6 autopsy No-HS hippocampi. The HS hippocampi showed sparse to scattered CD8-positive T-cells, rare CD4-positive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
34
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 37 publications
4
34
1
Order By: Relevance
“…These blood cells invade the hippocampal tissue and induce inflammation. Our data also support those reported by Lu (), who found a correlation between blood cell infiltration in the hippocampus and neuronal loss. This increase in BBB permeability can induce epileptogenesis, and sustain or aggravate epilepsy (Ho et al ), and increased BBB permeability can persist for several weeks, months, or even years after a long‐lasting seizure, and contribute to enhanced brain excitability (van Vliet et al ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These blood cells invade the hippocampal tissue and induce inflammation. Our data also support those reported by Lu (), who found a correlation between blood cell infiltration in the hippocampus and neuronal loss. This increase in BBB permeability can induce epileptogenesis, and sustain or aggravate epilepsy (Ho et al ), and increased BBB permeability can persist for several weeks, months, or even years after a long‐lasting seizure, and contribute to enhanced brain excitability (van Vliet et al ).…”
Section: Discussionsupporting
confidence: 93%
“…These blood cells invade the hippocampal tissue and induce inflammation. Our data also support those reported by Lu (2017), who found a correlation between blood cell Fig. 3 Analysis of H-kininogen processing in the serum/plasma of healthy subjects and patients with TLE.…”
Section: Discussionsupporting
confidence: 91%
“…Neuroinflammation with monocyte infiltration and microglial activation, as observed in rodent models of TLE, is also a frequently reported finding in patients with TLE ( 41 43 ). Thus, counteracting such inflammatory processes is considered a potential strategy for preventing or modifying epilepsy in patients at risk ( 2 , 3 , 44 47 ).…”
Section: Discussionmentioning
confidence: 63%
“…It is a major finding of the present study that the quantitative RT-PCR data not only confirmed the delayed T-cell response, but was also able to demonstrate that the increase was attributable to an enhanced CD8 + T-cell population. While the pathophysiological role of CD8 + cells has already been suggested in the rodent kainate model [ 34 ], there is recent evidence on the pathogenic role of CD8 + cells in autoimmune anti-GABA-B-receptor encephalitis in humans [ 36 ], but intriguingly, also human temporal lobe epilepsy [ 37 ].…”
Section: Discussionmentioning
confidence: 99%